Application of Mind Mapping Learning Model To Improve The Thematic Learning Outcomes of Students - Chintia Maharani; Fikriana (Program Doktor Pendidikan FKIP Universitas Lampung, 2025)
The problem in this study is the low learning outcomes of students grade VI at SD Negeri 3 Rajabasa Jaya. The purpose of research is to analyze the influence of applying of mind mapping learning model in improving students thematic learning outcomes. The research method used in this study was quasi-experimental group design, which the type used was nonequivalent control group design. The sample in this study was 52 students. The sample was determined using non-probability sampling technique. Then, the data were collected through test technique, documentation, and observation. The data is in the analysis using simple linear regression test to get r hitung 0,888 with n = 26 for α = 0,05 to get rtabel 0,374, so that rhitung > rtabel = 0,888 > 0,374.